Determination Of Solid Material Permittivity Using T-Ring Resonator For Food Industry - Al-Ahnomi, Rammah Ali Hussien; Mohd Bahar, Amyrul Azual; Hussein Al-Heghazi, Ammar Abdullah; Zakaria, Zahriladha; Mohd Yussof, Zulkalnain; Tole, Sutikno (Universitas Ahmad Dahlan (UAD), 2019)
In this paper, we present a simple design of a T-ring resonator sensor for characterizing solid detection. The sensor is based on a planar microwave ring resonator and operating at 4.2 GHz frequency with a high-quality factor and sensitivity. An optimization of the T-ring geometry and materials were made to achieve high sensitivity for microwave material characterizations. This technique can determine the properties of solid materials from range of 2 GHz to 12 GHz frequencies. Techniques of current microwave resonator are usually measuring the properties of material at frequencies with a wide range; however, their accuracy is limited. Contrary to techniques that have a narrowband which is normally measuring the properties of materials to a high-accuracy with limitation to only a single frequency. This sensor has a capability of measuring the properties of materials at frequencies of wide range to a high-accuracy. A good agreement is achieved between the simulated results of the tested materials and the values of the manufacturer’s Data sheets. An empirical equation has been developed accordingly for the simulated results of the tested materials. Various standard materials have been tested for validation and verification of the sensor sensitivity. The proposed concept enables the detection and characterization of materials and it has miniaturized the size with low cost, reusable, reliable, and ease of design fabrication with using a small size of tested sample. It is inspiring a broader of interest in developing microwave planar sensors and improving their applications in food industry, quality control and biomedical materials